Direitos humanos e currículo a partir da ética da vida - Pereira, Nilda da Silva (2012)
The aim of the thesis is to investigate the ethics as thought by Enrique Dussel as a curricular possibility for teaching human rights. It seeks to defend human rights teaching in basic education. All the pedagogic explicitness of human rights is based upon the Ethics of liberation, a critical ethics and a life ethics. We analyzed theoretically school projects selected through the National Award for Education, 2008 and 2010 editions, promoted by the Brazilian Ministry of Education, and Special Secretariat for Human Rights of Presidency of Republic of Brazil. We believe that these initiatives are good references about Brazil s education proposals on human rights in basic teaching. Those projects are concrete demonstrations that brazilian schools are building education in human rights. To develop the analysis, we highlight the contents of the projects worked; why they came; what were the real needs that led to its elaborations; theoretical processes; how the activities were launched; the results towards the transformation; and finally, relate the actions taken with the liberating praxis, linked to the ethics of life. The thesis provides aid to school in order to adopt ethics as a necessary reflection, to assist in discussions about violence, justice, racism, solidarity, ethics, etc., awakening the students for the exercise of citizenship and attention to human rights. The research is one of qualitative basis, a theoretical investigation of the ethics/morals from the philosopher Enrique Dussel